Differentiation of Lingxiaohua and Yangjinhua by chloroplast genome sequencing and DNA barcoding markers - Ngai, Hiu-Lam; Kong, Bobby Lim-Ho; Lau, David Tai-Wai; Shaw, Pang-Chui (Genome, 2023)
Lingxiaohua (Campsis Flos, Campsis grandiflora (Thunb.) K. Schum) is a medicinal herb used for promoting diuresis and treating blood-related disorders by the promotion of blood circulation. It also possesses anti-inflammatory and antioxidative properties. This non-poisonous plant is frequently confused with poisonous Yangjinhua (Daturae Metelis Flos, Datura metel Linnaeus) in the market, resulting in serious anticholinergic poisoning. The confusion of these two herbs is due to the similarity in their appearances. In our study, we compared the complete chloroplast genomes of the two plants and found that they are very different in terms of their gene content and gene arrangement. There were also significant differences in the number and repeating motifs of microsatellites and complex repeats. We used universal primers for the amplification of rbcL, matK, psbA-trnH, and ITS2 regions and successfully differentiated the two plants. Furthermore, we designed two pairs of primers based on the nucleotide differences in chloroplast genomes at the rps14 and rpoC1 regions to provide additional authentication markers. The universal primers and specific primers when used together can accurately discriminate Lingxiaohua and Yangjinhua.